ANALYSIS OF THE UTILIZATION OF E-LEARNING BY LECTURERS AT PANCA SAKTI BEKASI UNIVERSITY - Aryani, Rita; Holman Siahaan, Leroy (Sosiohumaniora, 2021)
This study aims to describe qualitatively about e-learning management in the current Covid-19 pandemic era. This research is a descriptive qualitative study that aims to define and describe phenomena that appear natural or artificial, focusing more on examining the character, quality, and phenomenon. Besides, the e-learning approach is an approach using technology distance learning. The e-learning utilization that is arranged using an electronic internet system that supports learning activities. The method used in this research is qualitative with descriptive analysis. Research subjects are Informantss who provide research data through interviews, observation, and documents. The Informantss in this study were lecturers at Panca Sakti Bekasi University. The Informantss were determined by purposive sampling technique. At the same time, the data analysis used in this research is descriptive. This research results in the finding that lecturers have carried out web e-learning with Moodle and face-to-face with zoom or google meet in managing learning during the Covid-19 pandemic. as numerous as 80% of speakers expressed that they utilized zoom, this was on the grounds that it was simpler to apply it straightforwardly, like instructing up close and personal classes. At that point, as numerous as 55% of Google Meet clients, the instructor expressed that Google Meet is not difficult to actualize on the grounds that the video is straightforwardly associated on the off chance that you as of now have a Google Mail account straightforwardly. Lastly, as numerous as 85% of teachers use Moodle, on the grounds that Moodle gives more highlights to learning exercises.